Digital Transformation and Human Capital Development: The Role of Digital Leadership, Employee Agility, and Sustainable Performance - Syarifuddin Syarifuddin; Muhammad Luthfi Siraj; Fahrian Arsyam Gultom; Zulfikar; Muhammad Novrizal Ramadhan (Economics and Business Journal (ECBIS), 2026)
Digital transformation has become a strategic priority for organizations seeking to enhance competitiveness and achieve sustainable performance in dynamic business environments. This study examines the effect of digital leadership on sustainable performance through the mediating role of employee agility within the context of human capital development. A quantitative explanatory approach was employed using survey data collected from employees involved in digital transformation initiatives. Data were gathered through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the direct and indirect relationships among the proposed constructs. The findings indicate that digital leadership significantly enhances employee agility by fostering adaptability, continuous learning, and responsiveness to technological change. Employee agility was found to have a strong positive effect on sustainable performance, suggesting that agile employees contribute substantially to organizational resilience, innovation capability, and long-term effectiveness. Furthermore, employee agility partially mediates the relationship between digital leadership and sustainable performance, demonstrating that the influence of leadership on sustainability outcomes operates largely through workforce adaptability. These results highlight the critical role of human capital development in digital transformation and provide empirical evidence that sustainable organizational performance can be achieved when digital leadership is effectively translated into agile employee behavior. The study contributes to the growing literature on digital transformation and human resource management by offering an integrated framework that links leadership, employee capabilities, and sustainability-oriented organizational outcomes.